Analysis of soil arching in piled embankments - Tham, Li Wen (2018)
Embankment constructed on soft ground has to be safe against excessive settlement and deep-seated slope failure. This project investigates the soil arching behaviour in piled embankments on soft ground. Stress is transferred from a yielding mass of the soft ground to adjacent piles with greater stiffness. The extent of the arching effect in piled embankments could be characterised by efficacy, competency and stress reduction ratio. Finite element analysis using PLAXIS 2D was conducted for a tributary area of a piled embankment in plane strain condition. The dimensions of the finite element models were varied and the results were compared with theoretical solutions and model tests reported in the literature. The theoretical solutions and the numerical analysis results are of reasonable agreement. The evolution arching patterns of the finite element models matched the patterns proposed for the respective model dimensions. The influence of various parameters such as pile width and pile clear spacing on the arching effect in the embankment were discussed in this paper. The results showed that the load carried by piles increases with an increase in the area ratio. A case study of the geogrid reinforced piled embankment was reviewed to highlight the effect of geogrid on arching in piled embankment. The limitations of the FEM model and recommendations for future work were discussed.